Prediction of Host-Derived miRNAs with the Potential to Target PVY in Potato Plants - Iqbal, Muhammad S.; Hafeez, Muhammad N.; Wattoo, Javed I.; Ali, Arfan; Sharif, Muhammad N.; Rashid, Bushra; Tabassum, Bushra; Nasir, Idrees A. (Frontiers in Genetics, 2016)
Potato virus Y has emerged as a threatening problem in all potato growing areas around the globe PVY reduces the yield and quality of potato cultivars. During last 30 years, significant genetic changes in PVY strains have been observed with an increased incidence associated with crop damage. In the current study, computational approaches were applied to predict Potato derived miRNA targets in PVY genome. PVY genome is about 9 thousand nucleotides approximately which transcribes 6 genes CI, NIa, NIb-Pro, HC-Pro, CP and VPg. A total of 343 mature miRNAs were retrieved from miRbase database and searched for their target sequences in PVY genes using minimum free energy (mfe), minimum folding energy, sequence complementarity and mRNA-miRNA hybridization approaches. Identified Potato miRNAs against viral mRNA targets have antiviral activities leading to either translational inhibition by mRNA cleavage/mRNA blockage or both. We have found 86 miRNAs targeting PVY genome at 151 different sites on PVY genome. Moreover, only 36 miRNA potentially targeted the PVY genome at 101 loci. CI gene of PVY genome was targeted by 32 miRNAs followed by complementarity by 26, 19, 18, 16 and 13 miRNAs respectively. Most importantly, we found 5 miRNAs (miR160a-5p, miR7997b, miR166c-3p, miR399h and miR5303d) could target CI, NIa, NIb-Pro, HC-Pro, CP and VPg genes of PVY. The predicted miRNAs can be used for development of PVY resistant potato crops in future.